Inclusão da pessoa com deficiência no Instituto Federal do Maranhão: políticas institucionais, desafios e conquistas do campus Pinheiro. - SILVA JÚNIOR, Ronaldo (2020)
It is noted that in Brazil, inclusive education policies have gained strength in their historical and political trajectory, consolidating, through legislative productions, the rights of people with disabilities. Thus, from 1990, the term “inclusion” was incorporated into educational discourses, as well as legislation aimed at special education. This study aimed to investigate how the Ifma - Campus Pinheiro operationalizes support services for students, aiming at the elimination and / or minimization of pedagogical and attitudinal barriers, ensuring them access, permanence and the guarantee of learning. The participants, in the context presented, were 12 civil servants and 20 students, who met the inclusion criteria in the research. The data collection instruments corresponded to semi-structured interviews and non-participating observations. The results reveal that: all participants have diverse views on inclusion, but all within the ideological principles from the perspective of Inclusive Education and / or “politically correct”; most participants are unaware of the actions developed by Ifma's NAPNE, as well as the role it plays in the context of including students from the target audience of Special / Inclusive Education; most of the participants did not interact with the students served by the Center; there is a lack of human resources and qualified professionals to operationalize the Inclusive Education process; most of the participants omit in relation to the activities developed by the Nucleus and credit it with the responsibility for inclusion. Despite all the difficulties and challenges to be overcome, the NAPNE of the Ifma / Campus Pinheiro, has done an important job for the inclusion of students with disabilities and / or with specific educational needs in the Maranhão region.